Annual World Bank Conference on Development Economics, Europe 2003 : Toward Pro-Poor Policies--Aid, Institutions, and Globalization - Tungodden, Bertil; Stern, Nicholas; Kolstad, Ivar (Washington, DC: World Bank and Oxford University Press, 2013)
The Annual World Bank Conference on Development Economics(ABCDE)-Europe 2003 presents selected papers from the fourth annual ABCDE-Europe meetings, held June 24-26, 2002, in Oslo, Norway. More than 350 eminent scholars and practitioners from 50 countries met to deliberate on the theme 'Towards Pro-Poor Policies'. The papers from sessions on aid, institutions, and globalization provide both a general overview of links between poverty, inequality, and growth, and address specific topics such as the Heavily Indebted Poor Countries Initiative for debt reduction. All consider the role of policies and institutions in development and poverty reduction. This volume contains an overview by Bertil Tungodden, Ivar Kolstad, and Nicholas Stern; papers on aid by Nicholas Stern, David Roland-Holst and Finn Tarp, Stephan Klasen, Lisa Chauvet and Patrick Guillaumont, and Jean-Pierre Cling, Mireille Razafindrakoto, and Fran?s Roubaud; papers on institutions by Mariano Tommasi, Mushtaq Khan, David Dunham, Stanley Engerman and Kenneth Sokoloff, Karla Hoff and Joseph Stiglitz; and papers on globalization by Jomo Sundaram, John Dunning, Antonio Spilimbergo, Juan Luis Londoo, and Miguel Szly, Andre Solimano, and Oded Stark.